Calcaneus Tenorraphy with Temporary Internal Immobilization in a Bitch - Da Silva Flores, Fabiano; Da Rosa, Carolina Cauduro; Costa, Eliesse Pereira; Cassanego, Guilherme Rech [UNESP]; Hörbe, Anna Vitória; Farencena, Fernanda Iensen; Corrêa, Luís Felipe Dutra (Universidade Federal do Rio Grande do Sul, 2023)
Background: In practical clinical and orthopedic surgery routine, the common calcaneal tendon has received attention from orthopedists, since most injuries in small animals are related to trauma. These Injuries can be partial or complete, and have a primary origin from trauma or a secondary origin from excessive stretching or chronic degeneration. The clinical manifestations include lameness, and postural changes. Imaging exams are used to confirm the diagnosis in addition to a clinical examination and the treatment approach is dependent on the severity of the injury. Therefore, this work aims to describe the treatment instituted in a canine diagnosed with rupture of the calcaneal tendon. Case: A 4-year-old bitch English Greyhound, weighing 19 kg, was treated at the HVU of UFSM with a history of pain and lameness in the left hind limb. During the anamnesis, the owner reported that the onset of these clinical manifestations occurred following a run 2 days prior to the consultation, without confirming whether there was a history of trauma or not. On clinical examination, pink mucous membranes and heart area and lung field were observed without apparent alteration on auscultation, heart beats per minute of 100, respiratory movements per minute of 30, temperature of 38.5°C and non-reactive lymph nodes. In the orthopedic examination, the patient presented grade III claudication with weight bearing, support of the limb in pinch, slight hyperflexion of the tarsus to movement and discomfort on palpation in the caudal region of the left hind limb, close to the calcaneal tuberosity. Therefore, the clinical suspicion was common calcaneal tendon rupture. A radiographic examination was requested to rule out fracture involvement. The radiographic image obtained did not reveal bone alterations compatible with fracture, then, an ultrasound examination was performed to evaluate the soft tissues. Ultrasound findings suggested partial rupture of the common calcaneal tendon, with complete rupture of the gastrocnemius tendon component, evidenced by loss of fiber parallelism architecture, change in echogenicity and thickening, indicating tendon discontinuity. Therefore, the animal was referred for surgery. Once the portion that was torn was identified, the fragments were prepared, removing a fragment of about one centimeter from the proximal and distal fragments. A modified Kessler suture pattern was used for tendon apposition, followed by suturing in a simple isolated pattern on the sheath portion and approximation of the unruptured tendon portion. Then, the synthesis of the subcutaneous tissue and the dermarrhaphy were performed with suture in a simple continuous pattern. After the tenorrhaphy, internal immobilization was performed with the introduction of a 2.5 mm Schanz pin, in the central region of the tarsus towards the tibial diaphysis, promoting a slight angulation, so that the limb remains in extension and does not overload the suture, promoting temporary tibiotarsal arthrodesis when fixing the calcaneal bone to the distal portion of the tibia. After 21 days with internal immobilization, the patient returned to remove the pin and an external immobilization was performed, instituted for 14 days, after which period the bandage was reviewed and removed, and the patient was discharged. Discussion: Calcaneal tendon tenorrhaphy technique with internal immobilization of the tibiotarsal joint with a Schanz pin was efficient for the case described. The canine recovered quickly and there were no trans and postoperative complications due to the accurate diagnosis of the disease and the adequate selection of the technique. Thus, the correct and agile diagnosis, using the most appropriate surgical method, was crucial for the patient return to routine activities satisfactorily.
Tenorrafia do calcâneo com imobilização temporária interna em uma cadela
Keywords: achilles tendon; dog; internal immobilization; tenorrhaphy